The United Kingdom - Grix, J.; Brannagan, P. M.; Houlihan, B. (Comparative elite sport development. Systems, structures and public policy, 2025)
The story of the development of elite sport in the United Kingdom offers a number of clear lessons for scholars of sport studies, and for countries wishing to emulate the UK's unprecedented success in publicly funded elite sport in the past two decades. As will become apparent, not all of the lessons are positive, as we argue that the UK's rise to global elite sports success has come at a price, both to athletes and society more widely. Before discussing the ingredients of the UK's sports system and how it has become characterised by strong government intervention at both the elite sport and mass sport levels, however, it is worth recalling the United Kingdom - or Britain's - unique role in the development of modern sport. Great Britain - and England in particular - is not only looked upon as the cradle of the industrial revolution, but also as the birthplace of modern sport. Indeed, many sports scholars, such as Guttmann (2004), understand the former to be a pre-requisite of the latter, although Szymanski (2008), argues, correctly, that it was the development of `associativity` (and in particular, `clubs`) in Britain as early as the 18th Century that laid the foundations for the development of modern sport. Thus, it was the combination of the transformation from a rural to an industrial society, with its emphasis on quantification, rationalisation and bureaucratisation (Guttmann, 2004), and the growth of associativity, that led to the spawning of myriad sports clubs in England that went on to influence the introduction of particular sports (rugby, football, athletics, etc.) and their organisation globally.